Тенденції створення системи розумного будинку - Білоцерківець, О. Г.; Зубков, О. В.; Зубков, А. О. (ХНУРЭ, 2021)
General overview of the work - says that in a smart home the main thing is the structure, algorithms and test software of a smart home, developed in Python, html and Java script for the Raspberry PI hardware platform. The approach used allows you to combine wired and wireless technologies, as well as easily add new subsystems and expand the functionality of already connected. The presence of several user interfaces and the ability to operate in low-speed Internet are important features in the Ukrainian market.
Keywords: розумний будинок; система автоматизована